Development of CASIN-Encapsulated PLGA-PEG Nanoparticles for Colorectal Cancer Treatment - Zhuraliyeva, Altyn; Umbayev, Bauyrzhan; Kadyr, Sanazar; Yermekova, Aislu; Makhambetova, Aigerim; Kaldybekov, Daulet; Mun, Ellina; Bulanin, Denis; Askarova, Sholpan (Eurasian Journal of Applied Biotechnology, 2025)
Background: CASIN, a selective Cdc42 inhibitor, shows strong antitumor potential in colorectal cancer (CRC) but its clinical translation is limited by rapid clearance and low bioavailability. To overcome these challenges, we developed poly(lactic-co-glycolic acid)-polyethylene glycol (PLGA-PEG-COOH) nanoparticles for efficient encapsulation and delivery of CASIN. Materials and methods: CASIN-loaded PLGA-PEG-COOH nanoparticles were prepared via one-step nanoprecipitation. The resulting particles were characterized for morphology, size, zeta potential, drug loading, encapsulation efficiency, and stability. Blood compatibility was assessed by hemolysis assays, while in vitro antitumor activity was evaluated in CRC cell lines (HT-29, SW620, HCT116) using CCK-8 assays. Results: The CASIN-PLGA-PEG nanoparticles were spherical and uniform, with an average size of 86 ± 1 nm. Encapsulation efficiency reached 66 ± 5% with a drug loading of 5 ± 1%. The formulation provided sustained drug release over 24 hours. Hemolysis assays demonstrated excellent biocompatibility (<1% hemolysis across tested doses). In vitro studies showed potent antiproliferative activity, with IC₅₀ values of 19.55 µM (HT-29), 9.33 µM (SW620), and 10.45 µM (HCT116). Conclusion: Encapsulation of CASIN into PLGA-PEG-COOH nanoparticles improved drug stability, release profile, and safety, while maintaining strong antitumor efficacy in vitro. This nanoplatform represents a promising strategy for targeted Cdc42 inhibition in CRC and warrants further investigation in in vivo models. Acknowledgement: This research has been funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP26100973) and Nazarbayev University, Collaborative Research Project (CRP) Grant No. 211123CRP1611. Key words: Colorectal cancer, Cdc42 inhibition, PLGA-PEG nanoparticles, Drug delivery.